EFFECTS OF THE TEMPERATURE ON THE OUTPUT VOLTAGE OF MONO-CRYSTALLINE AND POLY-CRYSTALLINE SOLAR PANELS - Hamzah Eteruddin; Atmam Atmam; David Setiawan; Yanuar Z. Arief (Universitas Mercu Buana, 2020)
People can make solar energy alternative energy by employing solar panels to generate electricity. The utilization of solar energy on a solar panel to generate electricity is affected by the weather and the duration of the radiation, and they will affect the solar panel’s temperature. There are various types of solar panels that can be found on the market today, including Mono-Crystalline and Poly-Crystalline. The difference in the material used needs to be observed in terms of temperature changes in the solar module. Our study’s findings showed that a change in the temperature would impact the solar panel’s output voltage, and the solar panel’s output voltage would change when it was connected to the load although the measured temperatures were almost the same.